The Effect of Android-Based Applications on First Aid Cardiopulmonary Resuscitation Skills: A Literature Review - Anggoroningsih, Yuni (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Coronary Heart Disease (CHD) is a leading cause of sudden cardiac arrest, with many cases occurring outside hospitals, known as Out-of-Hospital Cardiac Arrest (OHCA). Prompt and effective Cardiopulmonary Resuscitation (CPR) is essential to increase survival. Objective: This study aims to assess the role of Android-based mobile applications in enhancing CPR skills as part of first aid response. Methods: A literature review was conducted using nine peer-reviewed articles published between 2021 and 2024. Articles were sourced from PubMed and Google Scholar using keywords such as health education, basic life support, cardiac resuscitation, smartphone, and Android. Inclusion criteria included full-text English articles focusing on Android-based applications in CPR training or performance. The selection process followed PRISMA guidelines. Results: All nine articles met the criteria, with findings showing that Android-based CPR applications are effective tools for improving users’ CPR skills, especially in OHCA situations. These applications offer valid features that support both learning and practical implementation. Conclusion: Android-based applications significantly enhance first aid capabilities in cardiac and pulmonary resuscitation and serve as valuable tools for public health education and emergency readiness.